2017
DOI: 10.1038/s41598-017-03777-8
|View full text |Cite
|
Sign up to set email alerts
|

Shared and Specific Intrinsic Functional Connectivity Patterns in Unmedicated Bipolar Disorder and Major Depressive Disorder

Abstract: Identifying brain differences and similarities between bipolar disorder (BD) and major depressive disorder (MDD) is necessary for increasing our understanding of the pathophysiology and for developing more effective treatments. However, the features of whole-brain intrinsic functional connectivity underlying BD and MDD have not been directly compared. We collected resting-state fMRI data from 48 BD patients, 48 MDD patients, and 51 healthy subjects. We constructed voxel-wise whole-brain functional networks and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
30
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(33 citation statements)
references
References 80 publications
2
30
1
Order By: Relevance
“…Functional connectivity alterations in the temporal lobes between BD and MDD have been consistently reported by prior studies (He et al, 2016;Rive et al, 2016;Wang, Wang, Jia, Zhong, Niu et al, 2017;. Interestingly, previous structural MRI studies have reported decreased cortical thickness in temporal as well as frontal areas including the ACC in individuals with BD (Hanford, Nazarov, Hall, & Sassi, 2016).…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…Functional connectivity alterations in the temporal lobes between BD and MDD have been consistently reported by prior studies (He et al, 2016;Rive et al, 2016;Wang, Wang, Jia, Zhong, Niu et al, 2017;. Interestingly, previous structural MRI studies have reported decreased cortical thickness in temporal as well as frontal areas including the ACC in individuals with BD (Hanford, Nazarov, Hall, & Sassi, 2016).…”
Section: Discussionsupporting
confidence: 65%
“…Interestingly, previous structural MRI studies have reported decreased cortical thickness in temporal as well as frontal areas including the ACC in individuals with BD (Hanford, Nazarov, Hall, & Sassi, ). Wang, Wang, Jia, Zhong, Niu et al () examined a patient sample of currently depressed BD and MDD and proposed that their findings of an increased long‐range functional connectivity strength in the middle temporal gyrus in BD may display a compensatory mechanism to account for the impairments in gray matter structure (Wang, Wang, Jia, Zhong, Niu et al, ). We second this proposition and further hypothesize that the pattern we found in the frontal and temporal regions of our BD sample (high measures of centrality alongside low PL) may indicate structural deficits in these areas which the brain tries to compensate through a denser, more integrated functional organization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results are consistent with cumulative research showing similar clinical characteristics, brain functioning and predictors of remission for unipolar and bipolar depression. [54][55][56] Nevertheless, high quality replication studies in patients remitted from bipolar depression, specifically focusing on cognition would be beneficial. Current medication might have also influenced the results.…”
Section: Discussionmentioning
confidence: 99%
“…Simultaneously, graph theory analysis has been applied to explore brain network connectivity in psychiatric patients (21)(22)(23)(24)(25). Graphs are defined as sets of nodes and edges that represent system components and their mutual relationships (26).…”
Section: Introductionmentioning
confidence: 99%